(untitled) (Vietnam Journal of Community Medicine, 2023)
Objective: This study aims to investigate the impact of iron deficiency on NT-proBNP level and submaximal exercise capacity using the 6-minute walk test (6MWT) in heart failure patients with reduced left ventricular ejection fraction (HFrEF). Subjects and methods: All patients with HFrEF, who had achieved stable heart failure status underwent 6MWT. NT-proBNP, ferritin, and TSAT were also recorded. Patients were considered iron deficient when Ferritin < 100 mcg/L or met both criteria of Ferritin < 100 – 299 mcg/L and TSAT < 20%. Impaired submaximal exercise capacity was defined as 6MWT < 300m. Results: From December 2021 to April 2023, a total of 93 eligible cases were enrolled in the study, with an average age of 63.3. NT-proBNP levels were significantly higher in iron-deficient patients than in non-iron-deficient patients, with median values of 3447 and 1620 pg/nL, respectively (p=0.004). Univariate analysis revealed that the proportion of patients with reduced submaximal exercise capacity during the 6-minute walk test was higher in the iron-deficient group compared to the non-iron-deficient group (51.4% vs. 31.0%, p=0.05). Multivariate analysis showed that iron deficiency was independently associated with reduced submaximal exercise capacity (OR 3.247, p=0.041). Conclusion: In patients with HFrEF, iron deficiency is associated with reduced submaximal exercise capacity. NT-proBNP concentration in patients with iron deficiency is higher than those without.